Konstruksi Sosial Khatib dalam Masyarakat Islam (Studi Kasus di Kecamatan Kota, Baru Kota Jambi) - Isnanto, Dedy (Universitas Bondowoso, 2023)
Routines of religius and behavior propaganda of khatib was a social pheomenom that interested in Islamis society. Khatib as invites and reminders for human society, khatib didn’t appart from fundamental of the social conditions, took place by the factor that influence and developed dynamically. Rasionality, knowledge and the importance one in every where, come from various direction, was a driving force, as the limited and made a dinamic of social life khatib. Changed occur simulaneusly, through of dinameic that individual objectived and subectived without ever stopped the dialetic conditioned.